PENINGKATAN PROSES DAN HASIL BELAJAR IPAS MENGGUNAKAN MODEL PEMBELAJARAN TIME TOKEN PADA SISWA KELAS V SDIT AL-AKHYAR MUARA BUNGO - Putri Ayu Ningsih; subhanadri; dhini mufti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was motivated by the low process and learning outcomes of students in Science and Social Studies (IPAS), as indicated by the lack of participation during classroom activities. To address this issue, the cooperative learning model Time Token was implemented, which provides equal opportunities for students to speak through the use of tokens. The purpose of this research was to improve the learning process and outcomes of fifth-grade students at SDIT Al-Akhyar Muara Bungo. The method employed was Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection. The subjects were 19 students. Data were collected through teacher and student observations and learning tests, then analyzed using averages, percentages, and mastery learning. The results showed improvement in all aspects: teacher activity increased from 80.55% to 100%, student activity from 59.01% to 79.70%, and learning mastery from 47.05% (average score 50.78) to 78.94% (average score 90.52). These findings demonstrate that the Time Token model is effective in creating a democratic and participatory learning atmosphere, while also enhancing students’ motivation, communication skills, and IPAS learning outcomes. Therefore, this model can serve as an alternative instructional strategy to improve the quality of the teaching and learning process in elementary schools.